OVERCOMING AFFECTIVE FACTORS IN LANGUAGE LEARNING: THE ROLE OF MOTIVATION, ANXIETY, AND SELF-CONFIDENCE - Mubarok, Ahsin Fahmi; Nurindah, Siti (Transpublika Publisher, 2023)
Language learning often encounters challenges stemming from affective factors such as anxiety, low motivation, and a lack of self-confidence in using the target language. These factors can hinder the optimal achievement of language skills. This study aims to analyze various strategies that can be used to address affective factors in language learning. The research employs a literature review method, examining various relevant sources including journals, books, and scientific articles that discuss affective factors in language learning. This approach allows the researcher to identify and summarize existing findings on effective strategies for overcoming affective barriers. The results of the study indicate that strategies focusing on enhancing motivation, reducing anxiety, and developing self-confidence in using the target language can significantly help address affective barriers. The implementation of these strategies also contributes to the improvement of students' language skills.